Some indeﬁned integrals containing to the generalized hypergeometric function (2009)
In 1999 Nina Virchenko considered the generalization of the hypergeometric function of Gauss 2R 1 (a, b; c; τ; z) with a set of recurrence and differentiation formulas. In this work we evaluate some indefinite integrals that contain the generalized hypergeometric function and some pathological cases.